2014
DOI: 10.9734/acsj/2014/11082
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Mass Transfer Through a Porous Media of MHD Flow of Nanofluids with Thermal Radiation, Viscous Dissipation and Chemical Reaction Effects

Abstract: This work was carried out in collaboration between the two authors EH and BS. Author BS designed the study, wrote the protocol and wrote the first draft of the manuscript. Author EH deals with the calculation part, managed the analysis of the study and executed the program. Both authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Haile and Shankar [12] in their study on the effects of thermal radiation, viscous dissipation, and chemical reaction on heat and mass transfer of MHD flow of nanofluids through a porous medium observed that as the thermal radiation or viscous dissipation increases, it causes increase in temperature of the coolant fluid. Also, as the chemical reaction parameter increases, the concentration of fluid decreases in the boundary layer flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haile and Shankar [12] in their study on the effects of thermal radiation, viscous dissipation, and chemical reaction on heat and mass transfer of MHD flow of nanofluids through a porous medium observed that as the thermal radiation or viscous dissipation increases, it causes increase in temperature of the coolant fluid. Also, as the chemical reaction parameter increases, the concentration of fluid decreases in the boundary layer flow.…”
Section: Introductionmentioning
confidence: 99%
“…Sheikholeslami et al [16] in their study on the effects of magnetic field on the forced convection flow of nanofluids over a stretching surface concluded that momentum boundary layer thickness decreases as the magnetic parameter increases. However, in the research presented by Haile and Shankar [12], Uddin et al [13] and Sheikholeslami et al [16], the physical parameters of the coolant fluid such as fluids viscosity, thermal conductivity, diffusion coefficient, and fluid density were treated constantly. In fact, the temperature of the hot stretched sheet causes the temperature of the coolant fluid to change.…”
Section: Introductionmentioning
confidence: 99%
“…It is noticed that an increase in Pr results a decrease of the thermal boundary layer thickness and in general lowers average temperature within the boundary layer. The reason is that smaller values of Pr are equivalent to increasing the thermal conductivities, and heat is able to diffuse away from the heated plate more rapidly than for higher values of Pr [29]. Hence in the case of smaller Prandtl numbers as the boundary layers are thicker the rate of heat transfer is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of heat transfer acquired for a three‐dimensional MHD flow of a nanofluid accompanied by viscous dissipation over a stretching sheet in a rotating system was anatomized by Sheikholeslami et al Haile and Shankar inspected the chemically reactive MHD flow of nanofluids over a stretching sheet together with viscous dissipation and thermal radiation. El‐Aziz showed the unsteady flow characteristics of a viscous dissipative fluid with variable viscosity and a varying surface temperature over a stretching sheet.…”
Section: Introductionmentioning
confidence: 99%